Peningkatan Keterampilan Berbicara Melalui Metode Show and Tell dalam Pembelajaran Bahasa Indonesia Kelas IV SD Negeri 204/IV Kota Jambi - Annisa Ilma Fitri; Ilyas Idris (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to improve speaking skills through the show and tell method of grade IV students of SD Negeri 204/IV Jambi City. This research is a type of Classroom Action Research (PTK). The subject of the study was grade IV students of SD Negeri 204/IV Jambi City which amounted to 31 students. The data collection methods used are observation, tests, and documentation. The data analysis techniques used in this study are qualitative descriptive and quantitative descriptive. The learning action in cycle I did not experience obstacles in linguistic aspects such as vocabulary/expressions or diction. And non-linguistic aspects that include courage and attitude. Actions in cycle II have increased both in linguistic and non-linguistic aspects. The linguistic aspect includes speech, vocabulary/diction, and sentence determination. Non-linguistic aspects include fluency, mastery of material, courage and attitude. The improvement is shown by an increase in the value of students' speaking skills. The increase that occurred was the average score of student pre-action of 63.9 with a percentage of 19% completion, the average score in the first cycle of students was 70.3 with a percentage of completeness of 55%, the percentage of speaking skills action through the show and tell method was 57%, the average evaluation in cycle II was 78.8 with a percentage of 90% completeness. And this can also be seen from the percentage of speaking skills actions through the show and tell method, which is 80%.